On living in a capacitist city / society: pandemic times (Research, Society and Development, 2021)
The images of empty cities around the world at the beginning of the Pandemic are facts that become part of any analytical, theoretical and practical scenario and represent a contemporary challenge. In the same proportion, thinking about living in a capacitist city / society - before, during and after the pandemic - is very similar to the emptying of classrooms, the emptying of rights and the demands of segments of people with disabilities. As serious as these “emptyings” are those that refer to the concepts that continue to build barriers - architectural, communicational, attitudinal, sociocultural - in cities, schools, museums and leisure spaces in the cities in the Third Millennium. The challenge of addressing the issue of living different daily inaccessibilities in cities touches and raises discussions on the ethical-aesthetic level of the existential territories of people with disabilities. It is questioned, to what extent, the professionals who think and contribute to urban planning maintain concepts that support certain constructs of invisibility. The essay proposes to fly over the “city landscape” starting from theories of critical sciences and from the notion of the right of the sanitary subject. Are the planners of the Third Millennium thinking about cities without thinking about the people who inhabit them? And is the technical debate about accessibility sufficient to contemplate the demands for a life without discrimination due to disability? This essay seeks to collaborate with the public debate on the need for planned actions aimed at overcoming capacitism in order to implement public policies.